2022
DOI: 10.7759/cureus.30750
|View full text |Cite
|
Sign up to set email alerts
|

Is Neck Circumference Related to Other Anthropometric Measurements and Biochemical Parameters in Type 2 Diabetes?

Abstract: Background Obesity is one of the leading risk factors for developing type 2 diabetes mellitus (T2DM). Body mass index (BMI), waist circumference, and waist/hip ratio are anthropometric measurements used to diagnose obesity. In recent years, neck circumference, one of the anthropometric indicators used in assessing obesity, has come to the fore. This study investigates the relationship between neck circumference and other anthropometric measurements and specific biochemical parameters in T2DM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…HbA1c level was found to have a positive correlation with all anthropometric measurements and was positively affected by NC. Similar to our results, Kamarli et al found a positive correlation between NC and HbA1c levels [30]. The use of anthropometric measurements in the clinical management of DM can potentially provide benefits.…”
Section: Discussionsupporting
confidence: 92%
“…HbA1c level was found to have a positive correlation with all anthropometric measurements and was positively affected by NC. Similar to our results, Kamarli et al found a positive correlation between NC and HbA1c levels [30]. The use of anthropometric measurements in the clinical management of DM can potentially provide benefits.…”
Section: Discussionsupporting
confidence: 92%